2022
DOI: 10.1061/(asce)me.1943-5479.0000991
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Impact of COVID-19 on Construction Projects in Developing Countries: A Case Study of Iraq

Abstract: The outbreak of COVID-19 has impacted construction markets worldwide due to supply chain disruptions, workforce restrictions, and legislative changes. However, construction markets in developing countries are perceived to be more vulnerable to the challenges as-sociated with the pandemic. As such, the goal of this paper is to capture the impact of COVID-19 on construction projects in developing countries by considering the case of the Iraqi construction sector. A multistep research methodology was adopted by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…The proper documentation of responses to interruptions was suggested, which could be presented as evidence in the case of disputes or claims. The legal implications of COVID-19 in the construction industry have been discussed in other studies, and it is critical to ensure that contract documents are correctly interpreted and the teams on construction projects are aware of their roles in case of similar disruptions [54].…”
Section: Contract Languagementioning
confidence: 99%
“…The proper documentation of responses to interruptions was suggested, which could be presented as evidence in the case of disputes or claims. The legal implications of COVID-19 in the construction industry have been discussed in other studies, and it is critical to ensure that contract documents are correctly interpreted and the teams on construction projects are aware of their roles in case of similar disruptions [54].…”
Section: Contract Languagementioning
confidence: 99%
“…For instance, Ling et al (2022) revealed that construction projects suffered significant delays, cost overruns, and lower quality during the pandemic [ 8 ]. Al-Mhdawi et al (2022) found that the pandemic impacts involved contractual implications, the construction financial market, supply chain operations, and safety and risk management [ 9 ]. Jeon et al (2022) proposed the Purdue Index to assess the impact of COVID-19 pandemic on the American construction industry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several COVID-19-related studies specific to the construction industry. Some studies were focused on the impact of COVID-19 on the industry with regard to cost overruns and schedule delays [ 6 , 9 , 10 , 11 , 12 ]. For instance, Al-Mhdawi et al (2020) identified the impact of COVID-19 on construction projects in Iraq [ 10 ], while Jeon et al (2022) proposed the Purdue Index to assess the impact of COVID-19 on the US construction industry [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies were focused on the impact of COVID-19 on the industry with regard to cost overruns and schedule delays [ 6 , 9 , 10 , 11 , 12 ]. For instance, Al-Mhdawi et al (2020) identified the impact of COVID-19 on construction projects in Iraq [ 10 ], while Jeon et al (2022) proposed the Purdue Index to assess the impact of COVID-19 on the US construction industry [ 6 ]. Other studies explored the response strategies on pandemic impacts [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%